Body Schema plasticity of the arm: a systematic review of the methods and tasks - Zigrino, Anna; Zivi, Pierpaolo; Ferlazzo, Fabio; Sdoia, Stefano (Frontiers in Psychology, 2025)
IntroductionThe Body Schema represents the body in a way that allows for dynamic adaptation and integration of motor functions. It receives signals from different sensory modalities, including proprioception, vision and touch, to continuously update to plan and execute body movements. Moreover, it works synergistically with the Peripersonal Space, to enable efficient interactions with the outside world. To do so, the Body Schema temporarily alters itself, plastically adapting to different environmental requests. This work aims at reviewing and categorizing the most commonly used methods in the study of Body Schema, as an attempt to better understand its plasticity and adaptability in different circumstances.MethodsTwo prominent databases, namely Scopus and PsychInfo, were consulted. The eligibility criteria included studies conducted on humans, wherein the population was not clinical. Finally, studies were included in which the Body Schema was considered in isolation, without comparison to other body representations.ResultsThe selected papers were grouped into ten different categories, illustrating the various ways in which the Body Schema has been investigated.DiscussionDifferent methods to study the plasticity of the Body Schema are discussed. Moreover, it is hypothesized that two common denominators are fundamental for granting the Body Schema its functions: proprioception and sense of agency. Clinical and future research implications are discussed.